Front Cover: Multiplex identification of sepsis‐causing Gram‐negative pathogens from the plasma of infected blood. Issue 4 (14th February 2018) - Chung, Boram; Park, Chulmin; Cho, Sung‐Yeon; Shin, Juyoun; Shin, Sun; Yim, Seon‐Hee; Lee, Dong‐Gun; Chung, Yeun‐Jung
Abstract : DOI:10.1002/elps.201700405 The cover picture shows the strategy for developing stuffer‐free MLPA probes targeting specific genes for five Gram‐negative pathogens and extended‐spectrum β‐lactamase (ESBL) producing Gram‐negative pathogens, and shows resulting electropherograms of each Gram‐negative pathogens. This technology can be useful for early detection of major sepsis‐causing, drug‐resistant Gram‐negative pathogens, especially the major ESBL producing pathogens in the blood of sepsis patients.